Exploring a learning model for knowledge integration and the development of critical thinking among nursing students with previous learning: a qualitative study protocol - Chun-Chih Lin; Chin-Yen Han; Ya-Ling Huang; Han-Chang Ku; Li-Chin Chen (BMC Medical Education)
Abstract Students often struggle to apply their knowledge of bioscience to their care practice. Such knowledge is generally learned through remembering and understanding, but retention quickly fades. They also experience difficulty progressing to higher-order cognitive skills such as applying, analyzing, evaluating, and even creating, which are necessary to develop soft skills, such as critical thinking, in the care profession. In order to improve existing programs, there is a need to better understand students' prior learning experiences and processes. The proposed study will explore the previous learning experiences of nurses enrolled in a two-year nursing program at a Taiwan university and identify the challenges they face in integrating multidisciplinary knowledge and developing critical thinking competency. The study will adopt a constructivist grounded theory methodology to collect interview data. The findings are expected to improve higher cognitive learning performance and inform the revision of the two-year nursing curriculum.